Răspuns :
x-y = 96
x/y =5 de aici => x = 5 y
inlocuim pe x astfel obtinut (in functie de y) in prima ecuatie :
5 y - y = 96
adica 4 y = 96 =>
y = 96/4 , y= 24
apoi,
x - 24 = 96 , deci x = 96+24 x =120
x/y =5 de aici => x = 5 y
inlocuim pe x astfel obtinut (in functie de y) in prima ecuatie :
5 y - y = 96
adica 4 y = 96 =>
y = 96/4 , y= 24
apoi,
x - 24 = 96 , deci x = 96+24 x =120
a - b = 96
a : b = 5
⇒a = 5b
5b - b = 96
4b = 96
b = 96 : 4
b = 24
a = 5b ⇒ a = 5×24
a = 120
verificare
a-b=120-24=96
96=96
a : b = 5
⇒a = 5b
5b - b = 96
4b = 96
b = 96 : 4
b = 24
a = 5b ⇒ a = 5×24
a = 120
verificare
a-b=120-24=96
96=96